Análise proteômica comparativa de trofozoítos de Acanthamoeba antes e após reisolamento de córnea em modelo animal de ceratite amebiana - Ana Carolina Carvalho Silva (2017)
The free-living amoeba of the genus Acanthamoeba are ubiquitous protozoa isolated from the most varied environments. Eventually, they are found causing serious illness in humans. The most frequently infection caused by this protozoan is amoebic keratitis (KA), characterized by severe inflammation in the cornea that can lead to blindness. Knowledge about the parasitic proteins involved in the pathophysiological process may be useful to develop diagnostic and therapeutic strategies for CA. Thus, a comparative proteomic study was performed to identify proteins differentially expressed by Acanthamoeba trophozoites from long-term culture and from re-isolates obtained from KA-induced in a animal model. For this purpose, a strain of Acanthamoeba castellanii isolated from a patient with KA maintained in axenic culture in PYG medium since 2006 was used. Winstar rats where used to induce KA after intraestromal inoculation of 104 trophozoites. In order to define the most suitable method of obtaining proteins for the proteomic analysis, trophozoites of the longo-term culture ALX were submitted to the methods of protein extraction by sonication and freeze/thaw in the presence of detergent CHAPS. The sonication method was more adequate, resulting in two-dimensional maps of higher resolution. For the preparation of the two-dimensional gels of the evaluated cultures, total proteins of ALXltc, ALXrec1, ALXrec2 and ALXrec3 were focused. Subsequently, the already focused proteins were separated in the second dimension in polyacrylamide electrophoresis. Detection of differentially expressed proteins was performed using ImageMaster 2D Platinum software. Sixty-two spots were selected for mass spectrometry, of which 42 were identified in the Acanthamoeba specific database. Of these, eight hypothetical proteins with unknown function could be detected. Molecular function analyzes revealed that most proteins are associated with biological processes related to oxidation and molecular function of binding to the other protein. Through the representation in a heatmap of the analysis of differential expression between long-term culture and re-isolated cultures, it was possible to infer that Acanthamoeba modulates the expression of several proteins associated mainly to energy metabolism, proteolytic activity, control of gene expression, protein degradation or DNA methylation, response to DNA stress and repair, adaptation to the new environment, resistance to host immune mechanisms, and promotion of tissue damage.